The Effect of Resistivity of Used Cooking Oil on The Quality of Palm Cooking Oil - Masherlina Masherlina; Kerista Tarigan; Syahrul Humaidi (IKIP Mataram, 2023)
Indonesia is a country with a large area of oil palm plantations, so there are many factories for the production of cooking oil. Indonesian people use a lot of cooking oil because processed food in Indonesia is mostly fried which causes a lot of used cooking oil to be wasted. The purpose of this study was to determine the resistivity of used cooking oil on the quality of palm cooking oil which can be useful in the field of renewable energy and reduce environmental pollution due to excessive waste of palm cooking oil which can cause damage to aquatic ecosystems, pollute the soil, and cause health problems. Used cooking oil can be processed properly so it is not harmful to the environment and health. One of the steps in processing used cooking oil is to know its resistivity value as the beginning of the refining process. Used cooking oil has a resistivity value that contrasts with soil so it is easy to interpret. Thus it is expected to know the resistivity value of used palm cooking oil. The results of this test obtained the resistivity value of used cooking oil after frying five times, namely 13.320 Ohm meter.